Housing Facilities as Spatial Factors for Assessment of Inclusivity in Settlements (Case Study: Gampong Keudah, Banda Aceh) - Aghnia Zahrah; Sarvina Fitri Rizky; Kania Egidia (Jurnal Serambi Engineering, 2023)
Inclusivity is a principle that we often hear about in economic, social, and spatial development. The principle of inclusivity is one of the principles used to achieve balance in the 2030 Agenda, Sustainable Development Goals, United Nations. In settlements, the ability to be inclusive is indicated by the completeness of facilities and the affordability of locations. The affordability of the location in question is the ease of access to housing facilities in settlements. This accessibility will be a form of quantification that can be seen from the distance to each facility. Based on the quantification of distance, the level of spatial inclusivity in settlements is obtained. The method used is qualitative research with case studies in Gampong Keudah. The data in the form of distance collected from this qualitative research is the basis for looking at the level of inclusivity in Gampong Keudah. Through an assessment of inclusivity from a spatial perspective based on this measurement, it can be concluded that in general Gampong Keudah has developed towards inclusive settlements. This inclusivity assessment method can be considered for use in other locations.